Atividade leishmanicida do extrato bruto e frações obtidas das folhas de Tetradenia riparia (Hochstetter) Codd - Ferreira, Fabiana Borges Padilha (2016)
Leishmaniasis is an infectious disease, not contagious, caused by protozoa of the genus Leishmania, zoonotic and endemic character in 98 countries. The transmission occurs through sandfly bite Lutzomya genus. Leishmaniasis is one of the dermatologic diseases of great importance due to their ability to form deformations and also the psychological and social involvement. The Leishmania parasite has two evolutionary forms: the promastigote form, flagellate, which is in the digestive tract of the insect vector, and the amastigote form, aflagellate that develops intracellularly in mononuclear phagocytic cells of the vertebrate host. Treatment of leishmaniasis has shown therapeutic failures and severe adverse effects, which has led to the search for new antiparasitic agents with greater efficacy and lower toxicity. This study evaluated the effect of the crude extract and isolated fractions of Tetradenia riparia (Hochst.) Codd on promastigotes of Leishmania (Leishmania) amazonensis cytotoxicity human erythrocytes and J774.A1 macrophages. The results suggest that the crude extract and the fractions isolated T. riparia have leishmanicidal activity, with no toxicity to human erythrocytes, despite the toxicity J774.A1 macrophages, may be a promising alternative in the treatment of leishmaniasis.